Liquid Biphasic Electric Partitioning System as a Novel Integration Process for Betacyanins Extraction From Red-Purple Pitaya and Antioxidant Properties Assessment - Leong, Hui Yi; Chang, Yu-Kaung; Ooi, Chien Wei; Law, Chung Lim; Julkifle, Advina Lizah; Show, Pau Loke (Frontiers in Chemistry, 2019)
Nowadays, downstream bioprocessing industries are inclined toward the development of a green and high efficient bioseparation technology. Betacyanins are presently gaining higher interest in the food science processing as driven by their high tinctorial strength and health promoting functional properties. In this study, a novel green integration process of liquid biphasic electric partitioning system (LBEPS) was proposed for betacyanins extraction from peel and flesh of red-purple pitaya. Initially, the betacyanins extraction using LBEPS with initial settings was compared with that of liquid biphasic partitioning system (LBPS), and the results revealed that both systems demonstrated a comparable betacyanins extraction. This was followed by further optimizing the LBEPS for better betacyanins extraction. Several operating parameters including operation time, voltage applied and position of graphitic electrodes in the system were investigated. Moreover, comparison between optimized LBEPS and LBPS with optimized conditions of electric system (as post-treatment) as well as color characterization and antioxidant properties assessment were conducted. Overall, the betacyanins extraction employing the optimized LBEPS showed the significant highest values of betacyanins concentration in alcohol-rich top phase (Ct) and partition coefficient (K) of betacyanins from peel (99.256 ± 0.014% and 133.433 ± 2.566) and flesh (97.189 ± 0.172% and 34.665 ± 2.253) of red-purple pitaya. These results inferred that an optimal betacyanins extraction was successfully achieved by this approach. Also, the LBEPS with the peel and flesh showed phase volume ratio (Vr) values of 1.667 and 2.167, respectively, and this indicated that they have a clear biphasic separation. In addition, the peel and flesh extract obtained from the optimized LBEPS demonstrated different variations of red color as well as their antioxidant properties were well retained. This article introduces a new, reliable and effective bioseparation approach for the extraction of biomolecules, which is definitely worth to explore further as a bioseparation tool in the downstream bioprocessing.